2022
DOI: 10.3390/ijerph191912400
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationship between Cognitive Function and Health-Related Quality of Life among Middle-Aged and Older Patients with Diabetes in China: Digital Usage Behavior Differences

Abstract: Background: Cognitive function and health-related quality of life (HRQoL) are important issues in diabetes care. According to the China Association for Aging, it is estimated that by 2030, the number of elderly people with dementia in China will reach 22 million. The World Health Organization reports that by 2044, the number of people with diabetes in China is expected to reach 175 million. Methods: Cohort analyses were conducted based on 854 diabetic patients aged ≥45 years from the third (2015) and fourth (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…A large European study demonstrated that frailty is more common in older adult diabetics, who tend to be depressed in addition to having low self-health ratings [60]. A study of a cohort of diabetic patients in China reported a correlation between cognitive decline and quality of life [61]. Thus, older adult patients with diabetes not only require insulin injections, but also experience a variety of adverse effects that persist throughout their lives and do not improve their HRQOL.…”
Section: Relationship Between Aging Disease and Hrqolmentioning
confidence: 99%
“…A large European study demonstrated that frailty is more common in older adult diabetics, who tend to be depressed in addition to having low self-health ratings [60]. A study of a cohort of diabetic patients in China reported a correlation between cognitive decline and quality of life [61]. Thus, older adult patients with diabetes not only require insulin injections, but also experience a variety of adverse effects that persist throughout their lives and do not improve their HRQOL.…”
Section: Relationship Between Aging Disease and Hrqolmentioning
confidence: 99%
“…The doctor-patient relationship is a significant livelihood issue for each stage of social development, characterized by the different attributes of the times. The gradual tension in the doctor-patient relationship can lead to doctor-patient disputes [1], and the reason for this mainly stems from the cognitive differences between doctors and patients [2]. Therefore, easing the tension in doctor-patient relationships [3] and maintaining the regular order of medical services are questions we need to explore.…”
Section: Introductionmentioning
confidence: 99%
“…Following the same logic, recent research has consistently demonstrated the predictive role of QoL in cognitive impairment and dementia onset in older adults ( 35 , 39 ). A recent longitudinal study on middle-aged and older Chinese patients with diabetes, showed that participants’ health-related QoL (HRQoL) at Time 1 significantly predicted their cognitive impairment at Time 2 ( 40 ). Although previous mixed findings imply a bidirectional relationship between QoL and cognitive impairment, there is more evidence to support a predictive role of QoL on cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%